2012
DOI: 10.1186/1477-7819-10-146
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of clusterin expression in pancreatic adenocarcinoma

Abstract: BackgroundClusterin is known to be expressed in many human neoplasms, and is believed to participate in the regeneration, migration, and anti-apoptosis of tumor cells. However, few reports have addressed the relationship between the manifestation of clusterin and clinicopathologic parameters in pancreas cancer patients. In the present study, the authors investigated the expression of clusterin and its clinical significance in pancreatic adenocarcinoma.MethodsImmunohistochemical staining was performed for clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…APOJ expression was significantly upregulated in RCC tissues and could be an independent prognostic factor . APOJ overexpression in gastric cancer was associated with tumor progression and metastasis and in pancreatic carcinoma with lymph node metastasis . However, cytoplasmic APOJ expression was related to longer survival in NSCLC patients after surgery …”
Section: Apolipoproteins and Cancermentioning
confidence: 98%
“…APOJ expression was significantly upregulated in RCC tissues and could be an independent prognostic factor . APOJ overexpression in gastric cancer was associated with tumor progression and metastasis and in pancreatic carcinoma with lymph node metastasis . However, cytoplasmic APOJ expression was related to longer survival in NSCLC patients after surgery …”
Section: Apolipoproteins and Cancermentioning
confidence: 98%
“…A pioneering work by Scaltriti et al (2004) suggested that CLU counteracts cell migration and invasion. Conversely, more recent works from different laboratories indicate that it enhances cell migration in several cell models (Jin et al, 2012;Niu et al, 2012). Although there is some evidence that in macrophages, CLU promotes chemotactic migration through upregulation of matrix metalloproteinase-9 and NF-kB activation downstream of AKT and Erk1/2 (Shim et al, 2011;Shim, Kang, Choi, Park, & Min, 2012), hitherto its molecular mechanisms in prostate cells have remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…sCLU increase the resistance of HCC cells to chemotherapy by interacting with AKT and Bcl-2 / Bax pathway 25 . In pancreatic cancer, prostate cancer and other tumors, also observed increased sCLU expression, and increased resistance of tumor cells to chemotherapeutic drugs, while blocking the expression of sCLU protein increased the sensitivity of chemotherapy 26 , 27 . To analyze the relationship between GP73 and sCLU, we detected the expression of sCLU in OXA resistant HCC cell lines with different GP73 expression levels.…”
Section: Discussionmentioning
confidence: 97%